Hegel and the other : a study of the phenomenology of spirit - Kain, Philip J., 1943- (SUNY series in Hegelian studies., 2005)
"This volume by Philip J. Kain is one of the most accessibly written books on Hegel's Phenomenology of Spirit available. Avoiding technical jargon without diluting Hegel's thought, Kain shows the Phenomenology responding to Kant in far more places than are usually recognized. This perspective makes Hegel's text easier to understand. Kain also argues against the traditional understanding of the absolute and touches on Hegel's relation to contemporary feminist and postmodern themes."--Jacket